The Nexus of Contracts Revisited: Delineating the Business, the Firm, and the Legal Entity - Jonathan Hardman (Bond Law Review)
This article explores the economic concept of the ‘firm’ and the legal concept of the ‘company’. Having identified that the two do not entirely overlap, it detects an ambiguity in existing legal literature, and argues that the former is a better fit for corporate law’s ‘nexus for contracts’. It introduces the ‘business’ to describe all constituencies in the nexus of contracts not represented by the company. Reconceptualising base concepts in such a manner helps us reimagine existing argumentation structures – rather than arguing that non-shareholders should have rights in respect of the operation of the company, instead we can argue for limitations in respect of what the company can do in respect of the business. Three implications arise from this analysis. First, company law collectivises the power of certain constituencies only, and there is conceptual space to collectivise the power of the others. Second, this demonstrates differences in proximity – shareholders and directors should only interact through the company, and other constituencies have less of a claim to a say in the company’s running. Third, we can use this conceptualisation to argue that the company is holding assets as trustee for the wider firm rather than in its own right.